Climate justice: between Mammon and Mother Earth. Issue 4 (15th August 2016) - Meikle, Mandy; Wilson, Jake; Jafry, Tahseen
Abstract : Purpose: This paper contributes to the ethical debate over roles and responsibilities to address the injustices of climate change and its impacts. The current impasse over taking action may lie in the very different ways people view the world and their place in it. The aim is to explore some profound contradictions within differing strands of knowledge feeding into common understandings of climate justice. Design/methodology/approach: A literature review of appropriate peer-reviewed and 'grey' literature was conducted with a view to defining the term 'climate justice'. Findings: In addition to there being no single, clear definition of climate justice, a fundamental schism was found between what indigenous peoples want to see happen and what industrialised nations can do with respect to both the mitigation of, and adaptation to, climate change. Research limitations/implications: One limitation to defining climate justice, and reason for publishing, is the lack of peer-reviewed work on this topic. Practical implications: This paper has many practical implications, the most fundamental of which is the need to reach a consensus over rights to the Earth's resources. If humanity, within which there are many societies, chooses to follow a truly equitable path post-2015, industrialised countries and corporations will need to move away from 'endless growth economics'. Ways in which climate justice might be operationalised in future are considered, including the concept of a 'climate-justice' checklist. Originality/value: While the reconciliation proposed in this paper might be considered idealistic, unless we acknowledge the Earth's resources as limited, over-exploited and for all people to use sustainably, thus requiring a reduction in consumption by individuals relatively affluent in global terms, climate negotiators will continue talking about the same issues without achieving meaningful change.